Deficiency in Perlecan/HSPG2 during Bone Development Enhances Osteogenesis and Decreases Quality of Adult Bone in Mice - Lowe, Dylan A. (2014)
Perlecan/Hspg2 (Pln) is a large heparan sulfate proteoglycan abundant in the extracellular matrix of cartilage and the lacuno-canalicular space of adult bones. While Pln function during cartilage development is critical, evidenced by deficiency disorders including Schwartz-Jampel Syndrome and dyssegmental dysplasia Silverman-Handmaker type, little is known about its function in development of bone shape and quality. The purpose of this study was to understand the contribution of Pln to bone geometric and mechanical properties. We used hypomorph mutant mice that secrete negligible amount of Pln into skeletal tissues and analyzed their adult bone properties using micro-computed tomography and three-point-bending tests. Bone shortening and widening in Pln mutants was observed and could be attributed to loss of growth plate organization and accelerated osteogenesis that was reflected by elevated cortical thickness at older ages. This effect was more pronounced in Pln mutant females indicating a gender-specific effect of Pln deficiency on bone geometry. Additionally, mutant females, and to a lesser extent mutant males, increased their elastic modulus and bone mineral densities to counteract changes in bone shape, but at the expense of increased brittleness. In summary, Pln deficiency alters cartilage matrix patterning and, as we now show, coordinately influences bone formation and calcification.